F1. MENTALIZATION MEDIATES THE ASSOCIATION BETWEEN CHILDHOOD INTERPERSONAL TRAUMAS AND CLINICAL FEATURES OF SCHIZOID, SCHIZOTYPAL AND PARANOID PERSONALITY DISORDERS. (9th April 2019) - Berthelot, Nicolas; Lemieux, Roxanne; Gamache, Dominick; Savard, Claudia
Abstract: Background: Exposure to childhood interpersonal traumas is a significant risk factor for the emergence of schizoid, schizotypal and paranoid personality disorders (Bierer et al., 2003; Waxman et al., 2014). However, most children exposed to interpersonal traumas do not present such disorders during adulthood and the developmental mechanisms of risk remain to be clarified. The concept of mentalization may contribute to our understanding of these developmental trajectories considering that (1) mentalization is a definite protective factor in the context of trauma (Berthelot et al., 2014), (2) mentalization would play a key role in the emergence or exacerbation of psychosis and psychotic-related disorders (Debanné & Toffel, 2019), and that (3) mentalization was shown to mediate the association between childhood trauma and negative symptoms in psychotic patients (Weijers et al., 2018). Methods: A sample of 188 adults (78% women, Mage = 28.9, SDage = 5.22) from the community, including 69 participants with a history of abuse or neglect, completed self-report measures of interpersonal traumas (Childhood Trauma Questionnaires), personality disorders (Personality Diagnostic Questionnaire for DSM-IV revised), mentalization (Reflective Functioning Questionnaire) and mentalization of trauma (Trauma-Specific Reflective Functioning Questionnaire). Structural equation modeling (SEM) analyses were conducted to evaluate whether participants' mentalization abilities mediated the association between childhood interpersonal traumas and features of schizotypal, schizoid and paranoid personality disorders. Results: Adults exposed to childhood interpersonal traumas (M = 7.23, SD = 3.93) were more likely to report clinical features of the Cluster A personality disorders than participants without trauma (M = 4.47, SD = 2.95), t(106.92) = -4.97, p < .001. Indices of the SEM indicate a good fit for the theoretical model: CFI = 0.98, Normed Fit Index (NFI) = .95, RMSEA = .06 and χ2(8, N = 188) = 11.73 p = .16. Trauma-specific mentalization partially mediated the association between childhood trauma and features of schizotypal, schizoid and paranoid personality disorders. General mentalization was not associated with trauma but further contributed to Cluster A personality disorders. Discussion: The results suggest that mentalization is a protective factor against the emergence of clinical features of schizoid, schizotypal and paranoid personality disorders in people exposed to interpersonal traumas during their childhood. The ability to mentalize about traumatic experiences (i.e. the ability to reflect on the psychological and relational impacts of trauma, as well as to think of traumatic experiences in a coherent fashion, without denying it or taking the blame), more than general mentalization abilities (i.e. the ability to think of behaviors in terms of underlying mental states), was associated with the features of Cluster A personality disorders. Results suggest that timely delivered mentalization-based interventions with survivors of childhood traumas could protect against the emergence of disorders characterized by social awkwardness and social withdrawal.